Female migration phenology and climate conditions explain juvenile Red Knot (Calidris canutus rufa) counts during fall migration - Laura McKinnon; Lucie Schmaltz; Yves Aubry; Yann Rochepault; Christophe Buidin; Cedric Juillet (Resilience Alliance, 2022)
The management of avian populations at risk requires accurate estimates of vital rates across age and sex classes to effectively identify the most vulnerable demographic and support conservation actions. In the endangered Red Knot (Calidris canutus rufa), there are relatively few reliable estimates of reproductive success because they breed in such low densities across such a large and relatively inaccessible area in Arctic Canada. The purpose of this study is to test whether a migratory time lag between adult male and female knots during post-breeding southbound migration could be a reliable index of reproductive success for this species. If so, we expected to find a positive relationship between a time lag in male migration and the number or proportion of juveniles present at the same fall migration site. To test this hypothesis, we analyzed 13 years of capture-mark-recapture and census data from an important staging area during southbound migration. We found a strong and consistent age and sex-specific chronology; median passage dates for females were approximately 2 weeks earlier than males, with juveniles following 1 month later than adults of both sexes. For most years, there was a significant time lag of up to 27 days between females and males. However, we found no evidence to support that this time lag explained variation in the number of juveniles at the stopover site each year. Instead, we found that the timing of female migration along with an index of environmental conditions on the breeding grounds and during migration best described the proportion of juveniles present during migration. Overall, our results cast doubt on the reliability of the male migratory time lag as an indicator of breeding success.